Progressive plateau root form dental implant osseointegration: A human retrieval study. Issue 6 (4th November 2014) - Gil, Luiz F.; Suzuki, Marcelo; Janal, Malvin N.; Tovar, Nick; Marin, Charles; Granato, Rodrigo; Bonfante, Estevam A.; Jimbo, Ryo; Gil, Jose N.; Coelho, Paulo G.
Abstract Although preclinical and sparse human histology retrieval studies have shown that the interface between implant and bone is constantly remodeling, no human retrieval database has been developed to determine the effect of functional loading time and other clinical/implant design variables on osseointegration. The present study tested the hypothesis that bone‐to‐implant contact (BIC) and bone area fraction occupancy (BAFO) increase over functional loading time around dental implants. Due to prosthetic retreatment reasons, 93 human implant retrievals from the same manufacturer (Bicon LLC, Boston, MA, USA) were obtained over a period of approximately 15 years. The retrieved implants were under functional loading from 120 days to ∼18 years and were histomorphologic/metrically evaluated. BIC/BAFO were assessed as a function of multiple independent variables: implant surface type, diameter, length, jaw (maxilla/mandible), region (anterior/posterior), and time of functional loading. The results showed that both BIC and BAFO increased over time independently of implant design/clinical variables, supporting the postulated hypothesis. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1328–1332, 2015.